2021
DOI: 10.1021/acs.jafc.0c07004
|View full text |Cite
|
Sign up to set email alerts
|

Multiclass Analytical Method for Pesticide and Mycotoxin Analysis in Malt, Brewers’ Spent Grain, and Beer: Development, Validation, and Application

Abstract: A multiclass analytical method to determine pesticides and mycotoxins in beer-related matrices based on the dilute and shoot approach was optimized and validated according to the European guidelines SANTE/12682/2019 and EC/401/2006. Extraction used acidified acetonitrile at 1% (v/v) acetic acid, followed by horizontal shaking homogenization, centrifugation, freeze-out step for cleanup, another centrifugation, and injection into a high-performance liquid chromatography–tandem mass spectrometry system. Linearity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…For these water-soluble pesticides, there are many analytical methods using other chromatographic techniques such as high-performance liquid chromatography (HPLC), supercritical fluid chromatography (SFC), ultrahigh-performance liquid chromatography (UHPLC), or ultra-performance convergence chromatography (UPC 2 ). A lot of analytical methods using this technique have been proposed in recent years to analyze pesticide residues in cereals, malt, hop, and beer. ,,, …”
Section: Analysis Of Pesticide Residues In Raw Materials and Beermentioning
confidence: 99%
“…For these water-soluble pesticides, there are many analytical methods using other chromatographic techniques such as high-performance liquid chromatography (HPLC), supercritical fluid chromatography (SFC), ultrahigh-performance liquid chromatography (UHPLC), or ultra-performance convergence chromatography (UPC 2 ). A lot of analytical methods using this technique have been proposed in recent years to analyze pesticide residues in cereals, malt, hop, and beer. ,,, …”
Section: Analysis Of Pesticide Residues In Raw Materials and Beermentioning
confidence: 99%
“…Such studies show that the most pesticide concentrations are reduced during fermentation, pasteurization, clarification and filtration [18] , [28] , [41] , [62] . These studies have shown that final pesticide levels are generally low [50] . Nonetheless, some studies have raised consumer concern by reporting pesticide levels at levels above the limit allowed in drinking water [16] , [63] , and 92% of beers on the Latvian market have been shown to contain glyphosate [30] .…”
Section: Introductionmentioning
confidence: 99%
“…The method has been developed to measure the fraction of AFB 1 in solutions fast and facilely using ultra-high performance liquid chromatography (UHPLC) coupled with a diode array detector (DAD) or mass spectrometry (MS). It has been considered the golden approach for the measurement of AFB 1 fractions due to its high reproducibility and accuracy. , Nevertheless, the accuracy of this method largely relies on the certified reference materials (CRMs) of AFB 1 solutions prepared with various organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the aflatoxins, aflatoxin B 1 (AFB 1 , its chemical structure shown in Figure ) has been classified as a group I carcinogen by the International Agency Research on Cancer (IARC) . It has been widely found in agricultural commodities and foods, i.e., grains, vegetables, oils, milk, and eggs. In addition, AFB 1 is highly toxic and has been identified as hepatotoxic, carcinogenic, and teratogenic and can cause other specific symptoms. , Thus, AFB 1 is the subject of the regulations on foods and agricultural feeds. The corresponding legislation in over 80 countries has established the maximum permitted limit of AFB 1 in various foods and agricultural commodities aiming to protect human beings and animals. Accurate measurement of AFB 1 in various matrices is a prerequisite for effectively limiting the fractions of AFB 1 in agricultural products and foods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation